Penggunaan Media Pembelajaran Interaktif Berbasis Animasi Pada Mata Pelajaran Bahasa Inggris pada Pengenalan Huruf dan Angka Terhadap Motivasi Belajar Siswa Kelas I MIN 1 Pesisir Selatan - Asperina, Ratih; Putri, Lara Agnesta; Ekaputri, Yanti Nazmai; Fuja, Siti (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
The purpose of this study was to determine the effect of using animation-based interactive learning media in English subjects to introduce letters and numbers on the learning motivation of Grade I students of MIN 1 Pesisir Selatan. This study used a quantitative approach with a quasi-experimental research design. The population of this study amounted to 30 students and the sampling method used the census method, namely all members of the population were surveyed. This is done when the population is less than 30 students. Therefore, class A was used as the control class with a total of 15 students, and class B was used as the experimental class with a maximum of 15 students. The results of the normality and homogeneity tests showed that all data were normally distributed and uniform. The normality test results are sig. 0.120 > 0.05 for the experimental class and 0.198 > 0.05 for the control class, while the homogeneity test resulted in a significance value of 0.531 > 0.05. The results of hypothesis testing showed that the average learning motivation of the experimental class was 73.84 and the learning motivation of the control class was 57.57, namely 73.84> 57.57. Based on the results of the independent sample t test, the significance value of two factors (T-tail) < 0.000. 0,05. It can be concluded that there is an effect of using animated interactive learning media on first grade students.